Microbial water quality and health risk assessment in karst springs from Apuseni Mountains, Romania - Stupar, Zamfira; Levei, Erika Andrea; Neag, Emilia; Baricz, Andreea; Szekeres, Edina; Moldovan, Oana Teodora (Frontiers in Environmental Science, 2022)
In Apuseni Mountains (North-Western Romania), many of the inhabitants live in rural communities with limited or no access to the centralized and controlled water supply. This study assesses the microbiological quality of six karst spring waters from Bihor County used by rural communities as drinking water sources. Twenty-four water samples collected in January, April, June, and November 2021 were analyzed for E. coli, total coliforms, intestinal enterococci, Pseudomonas aeruginosa, and heterotrophic plate count at 37 °C and 22 °C. Standard microbiological methods based on the membrane filter technique or pour plate method were used for the microbiological characterization of the spring waters. The study revealed that the karst springs from the studied area present microbiological contamination. The microbiological parameters for five out of the six studied spring waters exceeded the maximum limits allowed by the 98/83/EC Directive. Quantitative Microbial Risk Assessment estimated the risk of waterborne diseases for both adults and children due to the E. coli contamination. High risk of infection/day (< 0.20 for adults and < 0.24 for children) as well as high risk of infection/year (< 0.25-1) were observed for all springs. The risk of illness caused by E. coli contamination of water ranged between 0.09 and 0.35 for five out of six groundwater sources. The local communities using the contaminated springs are submitted to daily and accumulated health threats. Therefore, preventive measures accompanied by continuous monitoring are necessary mainly for those water sources that are critical drinking water sources for the rural communities.